2017
DOI: 10.1016/j.actaastro.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Considering the collision probability of Active Debris Removal missions

Abstract: Active Debris Removal (ADR) methods are being developed due to a growing concern about the congestion on-orbit and sustainability of spaceflight. This study examined the probability of an on-orbit collision between an ADR target, whilst being de-orbited, and all the objects in the public catalogue published by the US Strategic Command. Such a collision could have significant effects because the target is likely to be located in a densely populated orbital regime and thus follow-on collisions could take place. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…For example, an assessment of these methods showed that the net, space-based laser, and robotic arm methods appear to be the most promising [69]. While some of the ADR proposals are to remove single larger-sized debris objects, there are also proposals to remove more pieces to save on the mission costs [51], [70], but a more extended ADR mission will also increase the collision probability with the ADR mission itself [71]. There is also a proposal that suggests the repositioning of large debris objects from crowded regions to a relatively less crowded altitude with a smaller lifetime [42].…”
Section: B Active Debris Removal (Adr)mentioning
confidence: 99%
“…For example, an assessment of these methods showed that the net, space-based laser, and robotic arm methods appear to be the most promising [69]. While some of the ADR proposals are to remove single larger-sized debris objects, there are also proposals to remove more pieces to save on the mission costs [51], [70], but a more extended ADR mission will also increase the collision probability with the ADR mission itself [71]. There is also a proposal that suggests the repositioning of large debris objects from crowded regions to a relatively less crowded altitude with a smaller lifetime [42].…”
Section: B Active Debris Removal (Adr)mentioning
confidence: 99%
“…The reward function g (•) reflects the threat of one particular debris. Some debris priority models focus on evaluating the thread of debris [39]- [41]. However, to evaluate the RL model and method in this paper, the reward function is only a performance indicator, so it is assumed to be the number of removed debris for validation.…”
Section: A Mission Descriptionmentioning
confidence: 99%
“…The best solution output is [1,30,39,19,59], which means the removal debris sequence is (1,3,4,2,6), and the removal time duration sequence is (1,22,19,19,19). The Q value of W/N also means the average reward, it is 5690/1500=3.7933 on the root node, and other Q values along the solution are shown in Table 4.…”
Section: Tests On Debris Set #1mentioning
confidence: 99%
“…By the end of January 2021, the total weight of space debris had reached 8400 tons, with 128 million debris with a size of 0.1-1 cm, about 90,000 debris with a size of 1-10 cm and 34,000 debris with a size greater than 10 cm [1]. The has been a rapid increase in the amount of space debris and the increasingly serious space debris environment poses a serious challenge to the sustainable development of space activities [2][3][4][5][6][7]. Active removal of space debris has become a common consensus [8].…”
Section: Introductionmentioning
confidence: 99%